Proceedings of the Norwegian Environmental Toxicology Symposium, 2018 (NSFT - Norsk Selskap for Farmakologi og Toksikologi, 2018)
Abstract book from the Proceedings of the Norwegian Environmental Toxicology Symposium, Svalbard, 2018, arranged by NSFT: http://nsft.net/7th-norwegian-environmental-toxicology-symposium-nets-.